The production of ejectives in German and Georgian. (November 2021) - Brandt, Erika; Simpson, Adrian P.
Highlights: Ejectives can occur as phonological sounds, e.g. in Georgian, and epiphenomenal productions, e.g. in German. Epiphenomenal ejectives in German are the result of an overlap of two articulatory gestures. Georgian ejective production highly depends on the sentence position. Ejective production in both languages may be realized by a pulmonic airstream after oral closure. Abstract: This paper aims to shed light on the textbook description of ejective production through an analysis of the articulatory measures intraoral pressure and larynx height in a data set of phonological Georgian ejectives and epiphenomenal German ejectives. By comparing articulatory mechanisms for ejective production in these two languages, we aim to learn about how ejectives gain phonological status in a language. 14 female German speakers and 13 female Georgian speakers are recorded in a multi-channel experimental set-up. We collect intraoral pressure (IOP) data, an electroglottographic signal and larynx trace using a dual-channel electroglottograph, as well as audio data. We control for place of articulation, vocalic context, word and sentence position, as well as for plosive duration in our analysis. Generalized additive mixed-models are used for statistical analysis. In Georgian, larynx height highly depends on the word and sentence position of the ejective. We find evidence for the hypothesis that pressure buildup after oral closure may be realized by a pulmonic airstream in both Georgian and German ejective production. Sentence-internal Georgian ejectives are produced with lower IOP peak and less steep IOP increase than sentence-initial ejectives. Epiphenomenal ejectives in German are not produced with raised larynx and show lower average IOP than plosives in control conditions.